2018
DOI: 10.1007/s12035-018-1231-5
|View full text |Cite
|
Sign up to set email alerts
|

Biliverdin Reductase-A Mediates the Beneficial Effects of Intranasal Insulin in Alzheimer Disease

Abstract: Impairment of biliverdin reductase-A (BVR-A) is an early event leading to brain insulin resistance in AD. Intranasal insulin (INI) administration is under evaluation as a strategy to alleviate brain insulin resistance; however, the molecular mechanisms underlying INI beneficial effects are still unclear. We show that INI improves insulin signaling activation in the hippocampus and cortex of adult and aged 3×Tg-AD mice by ameliorating BVR-A activation. These changes were associated with a reduction of nitrosati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
72
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 88 publications
7
72
1
Order By: Relevance
“…Thus, it is clear that BVRA can impact insulin signaling through its interactions with AKT. Others have shown that the loss of BVRA in the brain causes insulin-resistance that occurs in Alzheimer's disease [60][61][62]. However, the loss of BVRA in obesity can result in hyperactivation of insulin signaling [18].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is clear that BVRA can impact insulin signaling through its interactions with AKT. Others have shown that the loss of BVRA in the brain causes insulin-resistance that occurs in Alzheimer's disease [60][61][62]. However, the loss of BVRA in obesity can result in hyperactivation of insulin signaling [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, impairment of biliverdin reductase is a common clinical feature in the symptomatology of AD and type 2 diabetes mellitus (T2DM). These reports suggest that biliverdin reductase is important in the prevention of AD and T2DM [8,9,13]. Even though biliverdin reductase is involved in various diseases, the role of this enzyme in ischemic insults has not been investigated yet.…”
Section: Discussionmentioning
confidence: 99%
“…Biliverdin reductase and bilirubin are involved in various diseases, including brain damage and protection against oxidative stress-induced neuronal injury [6][7][8][9]. BLVRA has an antioxidant function on ROS via production of bilirubin.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal subfields and electrode positions were identified with the aid of 4ϫ and 40ϫ water-immersion objectives on an upright microscope equipped with differential interference contrast optics under infrared illumination (BX51WI; Olympus) and video observation (BTE-B050-U CMOS camera; Mightex). Neighboring pairs of pyramidal cells were recorded simultaneously in CA1 by single stimulating bipolar tungsten electrode (FHC) placed on the Schaffer collateral fibers, as described previously (Barone et al, 2019). Slices were incubated in artificial CSF (ACSF) containing the following (in mM): 119 NaCl, 2.5 KCl, 4 CaCl 2 , 4 MgCl 2 , 1 NaH 2 PO 4 , 26 NaHCO 3 , 11 D-glucose, and 0.005 2-chloroadenosine, gassed with 95% O 2 /5% CO 2 .…”
Section: Dual Whole-cell Recordingsmentioning
confidence: 99%